Interactions between physicians and the pharmaceutical industry generally and sales representatives specifically and their association with physicians’ attitudes and prescribing habits: a systematic review - Fickweiler, Freek; Fickweiler, Ward; Urbach, Ewout (BMJ open, 2017)
ObjectivesThe objective of this review is to explore interactions between physicians and the pharmaceutical industry including sales representatives and their impact on physicians’ attitude and prescribing habits.Data sourcesPubMed, Embase, Cochrane Library and Google scholar electronic databases were searched from 1992 to August 2016 using free-text words and medical subject headings relevant to the topic.Study selectionStudies included cross-sectional studies, cohort studies, randomised trials and survey designs. Studies with narrative reviews, case reports, opinion polls and letters to the editor were excluded from data synthesis.Data extractionTwo reviewers independently extracted the data. Data on study design, study year, country, participant characteristics, setting and number of participants were collected.Data synthesisPharmaceutical industry and pharmaceutical sales representative (PSR) interactions influence physicians’ attitudes and their prescribing behaviour and increase the number of formulary addition requests for the company’s drug.ConclusionPhysician–pharmaceutical industry and its sales representative’s interactions and acceptance of gifts from the company’s PSRs have been found to affect physicians’ prescribing behaviour and are likely to contribute to irrational prescribing of the company’s drug. Therefore, intervention in the form of policy implementation and education about the implications of these interactions is needed.